A stranger in a strange land: a perspective on archaeological responses to the palaeogenetic revolution from an archaeologist working amongst palaeogeneticists. Issue 4 (8th August 2019) - Booth, Thomas J.
ABSTRACT: Here I provide a perspective on the palaeogenetic revolution from an archaeologist who has spent the last four years working alongside palaeogeneticists. I address the questions posed for this journal issue by talking through some of the recurrent comments I have encountered from archaeologists regarding the results of palaeogenetic analyses, particular the renewed emphasis on migrations influencing certain cultural transitions in later prehistoric Europe. Most of the antagonism between the two approaches stems from misunderstandings regarding each other's implicit methods, questions and epistemologies. Palaeogenetic studies are far from infallible, particularly when it comes to characteristing the archaeological evidence, but many of the common points of criticism levelled at them by archaeologists are often misguided. If we can move past a climate antagonism and suspicion around palaeogenetics, synthesis with the archaeological evidence provides tantalizing opportunities for developing richer understandings of the archaeological record and the lives of people in the past.